1994
DOI: 10.1172/jci117599
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of insulin action and glucose effectiveness in diabetic and nondiabetic humans.

Abstract: Insulin concentrations in humans continuously change and typically increase only when glucose also increases such as with eating. In this setting, it is not known whether the severity of hepatic and extrahepatic insulin resistance is comparable and whether the ability of glucose to regulate its own uptake and release is defective in non-insulin-dependent diabetes mellitus (NIDDM). To address this question, NIDDM and nondiabetic subjects were studied when glucose concentrations were clamped at either 5 mM (eugl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 60 publications
3
53
1
Order By: Relevance
“…Our results may appear to contradict those of Baron et al [16] and Alzaid et al [55], who concluded that the mass action effect of glucose is normal in NIDDM subjects. However, there were several differences between their experimental protocols [16,55] and our own.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results may appear to contradict those of Baron et al [16] and Alzaid et al [55], who concluded that the mass action effect of glucose is normal in NIDDM subjects. However, there were several differences between their experimental protocols [16,55] and our own.…”
Section: Discussioncontrasting
confidence: 99%
“…However, there were several differences between their experimental protocols [16,55] and our own. In Baron's study [16] fasting hyperglycaemia was clamped during suppression of plasma insulin levels by somatostatin infusion and glucose turnover measurements were obtained with tracer technique.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, in NIDDM, the importance of glucose effectiveness to glucose tolerance may be substantial. Insulin secretion is suppressed (26), and insulin resistance is usually profound, such that within the physiologic concentration range insulin has little measurable effect to increase R d (27,28). Thus it follows that glucose effectiveness is the primary determinant of R d in the type 2 diabetic state (29), as confirmed by Alzaid and colleagues (27) from meal tolerance studies in which glucose balance across muscle bed were assessed.…”
Section: Discussionmentioning
confidence: 90%
“…This was done in an effort to minimize the change in plasma glucose specific activity, thereby enabling accurate measurement of glucose turnover (3,15). This resulted in a mean plasma glucose specific activity that averaged Ϫ3.2 Ϯ 11.2, 4.7 Ϯ 7.0, and 15.1 Ϯ 4.7% of basal on the euglycemia, sustained-hyperglycemia, and profile study days, respectively.…”
Section: Subjectsmentioning
confidence: 99%